Implantação da ferramenta BI no sistema de inteligência de negócios para tomadas de decisões no processo produtivo da empresa Makauta em Manaus - CAVALCANTE, Luiz Carlos Monteiro (Universidade Federal do Pará, 2023)
The evolution of the production process, formerly "shop floor", has been significant in recent decades. Many projects have been developed for the deployment of ―industry 4.0‖. Major investments have been made in infrastructure, automation, training and information systems, making this sector a strategic area in a timely manner for companies. ―Shop floor‖ today generates a large amount of data that, because it is scattered or disorganized, is not used to its full potential as a source of information for decision making. Thinking about this under-utilization of the information provided in the production process, this paper proposes the implementation of a Business Intelligence system through the use of the Qlik Sense tool, applied specifically to the treatment of ―shop floor‖ data. The goal is to develop a system that uses the data resulting from the production process and transforms it into information that helps managers make timely decisions in this process in order to improve the company's competitiveness.